Ion-induced dipole interaction in confining cavities - Perá, Leonan Augusto Massete [UNESP]; da Silva, Josimar Fernando [UNESP]; Drigo Filho, Elso [UNESP] (Elsevier, 2025)
This work presents the solution for the ground state of the confined ion-induced dipole potential using the Variational Method with a trial eigenfunction derived from the Supersymmetric Quantum Mechanics formalism to mimc the interaction between the ferrous ion and the oxygen molecule in hemoprotein cavities, analyzing the stability of this interaction for different cavity volumes. This eigenfunction incorporates terms for the confinement radius and excluded volume of the system. Results show an anomalous effect on the ground state energy in smaller accessible volumes. We discuss the stability of the bond when compared to the termal energy of the system. To validate the VM, we also calculated energies using the Finite Element Method, finding a percentage error of less than 0.1%. The proposed model is interesting due to the low percentagem error compared to FEM and the simplicity of the eigenfunction, contributing to studies on hemoprotein interaction stability.
Keywords: Confined systems; Ion-induced dipole interaction; Supersymmetric Quantum Mechanics; Variational method